Skoring Pre-Operasi Memprediksi Keganasan pada Pasien dengan Ikterus Obstruktif di Rumah Sakit Hasan Sadikin - Benita Putri Permata; Reno Rudiman; Tommy Ruchimat (Lembaga Pengembangan Kinerja Dosen, 2025)
Obstructive jaundice is commonly caused by both benig n and malignant hepatobiliary disorders. Early identification of malignancy remains challenging, especially in settings with limited access to advanced diagnostic modalities. To evaluate the diagnostic accuracy of the Probability of Malignancy (P-MAL) score in predicting malignant causes of obstructive jaundice. A prospective analytic study was conducted at Dr. Hasan Sadikin General Hospital, Bandung, from December 2024 to August 2025. Forty-eight patients with obstructive jaundice were enrolled consecutively. Clinical characteristics and laboratory parameters were collected to calculate the P-MAL score. Final diagnosis was confirmed by histopathological examination. Diagnostic performance was assessed using receiver operating characteristic analysis. Among 49 patients, 15 (31.3%) were diagnosed with malignant obstructive jaundice. Patients with malignancy were significantly older and had higher levels of total bilirubin and alkaline phosphatase. The P-MAL score demonstrated good diagnostic accuracy with an area under the curve of 0.832 (95% CI 0.720–0.945; p < 0.001). A cut-off value ≥0.9994 yielded a sensitivity of 93.3% and specificity of 54.5%. The P-MAL score shows good accuracy for predicting malignancy in obstructive jaundice and may serve as a useful preoperative screening tool.